Management of postoperative nausea and vomiting: focus on palonosetron - Neil A Muchatuta; Michael J Paech (Dove Medical Press, 2008)
Neil A Muchatuta1, Michael J Paech21Department of Anaesthesia and Pain Medicine, King Edward Memorial Hospital for Women, Perth, Western Australia; 2Pharmacology and Anaesthesiology Unit, The School of Medicine and Pharmacology, The University of Western Australia, Perth, Western AustraliaAbstract: Postoperative nausea and vomiting (PONV) remains a significant problem in modern anesthetic practice, with an incidence in high-risk groups of up to 80%. In addition to being unpleasant and distressing for the patient, PONV has the potential to adversely affect patient and surgical outcomes. Advances in PONV prophylaxis over recent years include using non-pharmacological means to reduce baseline risk, a change to less emetogenic anesthetic techniques and the combination of multiple antiemetic drugs. The 5-hydroxytryptamine-3 (5-HT3) antagonists have proven a particularly valuable addition to the armamentarium against PONV. Palonosetron is a second-generation 5-HT3 antagonist that has recently been approved for prophylaxis against PONV. It has unique structural, pharmacological and clinical properties that distinguish it from other agents in its class. This review summarizes current evidence on PONV prophylaxis, reviews the 5-HT3 antagonists in particular and focuses on the established and future roles of palonosetron.Keywords: palonosetron, antiemetics, 5-HT3 antagonists, postoperative nausea and vomiting